1988
DOI: 10.1104/pp.88.4.1332
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Utilization by Suspension Cultures and Somatic Embryos of Daucus carota L. Measured by 13C NMR

Abstract: The uptake and utilization of sucrose by embryogenic suspension cultures of carrot (Daucus carota L.) growing in the presence of 2,4-D and by somatic embryos derived from these cultures was monitored using (13)C nuclear magnetic resonance. The exogeneously supplied sucrose was completely hydrolyzed before cell entry; glucose was taken up preferentially when the cells were cultured in the presence of 2,4-D, while glucose and fructose were utilized at similar rates by somatic embryos in the absence of 2,4-D. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 18 publications
3
16
0
Order By: Relevance
“…However, the C-1 peak was not detected when either 1-13 C-or 6-13 C-labeled glucose was used as the carbohydrate source. Second, the absence of the [4-13 C]malate peak in the [6][7][8][9][10][11][12][13] C]glucose experiment confirmed that 4-13 C resonance does not originate from the malate pool participating in the TCA cycle.…”
supporting
confidence: 55%
See 3 more Smart Citations
“…However, the C-1 peak was not detected when either 1-13 C-or 6-13 C-labeled glucose was used as the carbohydrate source. Second, the absence of the [4-13 C]malate peak in the [6][7][8][9][10][11][12][13] C]glucose experiment confirmed that 4-13 C resonance does not originate from the malate pool participating in the TCA cycle.…”
supporting
confidence: 55%
“…Peaks at 103.4 and 102.6 were not detected until 150 hs after perfusion with C-1-labeled glucose but increased continuously thereafter. [6][7][8][9][10][11][12][13] C]Glucan resonances are also observed to build up in the 1-13 C-labeled experiment. Similarly, a build up of the 1-13 C-labeled glucans is observed (Fig.…”
Section: Glucansmentioning
confidence: 86%
See 2 more Smart Citations
“…can be done with natural abundance 13 C NMR (25), enriched 13 C NMR (25-27) and 1 H NMR (28). This quantification includes both intracellular and extracellular levels, which can be determined separately by measurements of the medium and of the biomass (25,27). The fate of a particular 13 C enriched substrate is useful to label metabolic pathways, especially for systems in which the metabolic pathways are not elucidated completely.…”
Section: Carbon Metabolitesmentioning
confidence: 99%